How English Texts Work for Deaf Learners: A View from Systemic Functional Linguistics’ Transitivity System - Zharfa, Ratri Izzati; Anjaniputra, Agung Ginanjar (ELE Reviews: English Language Education Reviews, 2025)
This study examines how experiential meaning is realized in an Indonesian government-published English textbook for eleventh-grade deaf students in Special Senior High Schools (SMALB). While this meaning concerns who is doing what in certain circumstances, it can also investigate what happenings are involved, given that aural happenings pose significant linguistic and pedagogical difficulties among deaf students in accessing learning materials. However, little is known about the instructional content in such a textbook. Using the transitivity system from Systemic Functional Linguistics (SFL) to capture the language realizations and insights of the social model of disability in coping with structural barriers, this study examined clauses as the unit of analysis, comprising 176 short commands and 87 brief dialogues. The findings highlight the need to accommodate the nature of deaf students, as both text types lack adequate linguistic diversity and multimodal support, thereby limiting accessibility and engagement. These findings reflect structural barriers in the textbook design. This study recommends revising the command structure, diversifying participant roles and circumstantial elements, and integrating visual strategies such as sign language models, gestures, and contextual images. This study highlights that transitivity analysis can be harnessed to inform appropriate doings and experiences related to learning, contributing to inclusive English language instruction and equitable learning experiences for deaf students.